2006
DOI: 10.1117/12.695306
|View full text |Cite
|
Sign up to set email alerts
|

Reduced measurement uncertainty of white-light interferometry on rough surfaces

Abstract: In white-light interferometry at rough surfaces ("Coherence radar") the measuring uncertainty is physically limited by the arbitrary phase of the individual speckle interferograms. As a consequence, the standard deviation of the measured shape data is inevitably given by the (optically unresolved) roughness of the surface. The statistical error in each measuring point depends on the brightness of the corresponding speckle; a dark speckle yields a more uncertain measurement than a bright one. If the brightness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…More precisely, reflectivity can influence white light interferograms by affecting the intensity, contrast, and visibility, and potentially introducing phase shifts in the interference fringes. Gross et al [13] demonstrated that the statistical error of each measurement location depends on the brightness of the associated speckle; a dark speckle gives a more uncertain measurement than a bright one. If the brightness is lower than the camera's noise threshold, the measurement fails completely, and an outlier appears that leads to a NaN value.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, reflectivity can influence white light interferograms by affecting the intensity, contrast, and visibility, and potentially introducing phase shifts in the interference fringes. Gross et al [13] demonstrated that the statistical error of each measurement location depends on the brightness of the associated speckle; a dark speckle gives a more uncertain measurement than a bright one. If the brightness is lower than the camera's noise threshold, the measurement fails completely, and an outlier appears that leads to a NaN value.…”
Section: Introductionmentioning
confidence: 99%